Global and Local Visual Processing in Rate/Accuracy Subtypes of Dyslexia - Goldstein-Marcusohn, Yael; Goldfarb, Liat; Shany, Michal (Frontiers in Psychology, 2020)
Words are processed in both a global and local manner. Studies on global versus local processing styles in individuals with and without dyslexia are inconclusive. In the present study, we investigated whether distinct patterns of global/local visual processing were associated with more precisely defined dyslexia profiles. Previous studies on dyslexia provide evidence of accuracy- and rate-based subtypes, with impairment in one dimension alongside normal performance in the other. In the current study, three groups of adult readers: rate disability, accuracy disability, typical development, were presented with nonlinguistic global /local congruency task. The results revealed that the rate disability group had deficiencies performing the global task while the accuracy disability group had deficiencies in the local task. These results are discussed in the context of global/local word processing and in relation to dyslexia. Specifically, they suggest that global /local disassociation is observed between different types of dyslexics and imply that practitioners should modify their treatment based on the specific deficiency.